Role of Oxidative Stress in various stages of Psoriasis - Fearoz Khan , Zahoor Ahmed , Hajira Ishaq , Sadia Azam Khan , Mohammad Iqbal , Mohammad Tayyab Ahmad , Muhammad Umar, Fearoz Khan , Zahoor Ahmed , Hajira Ishaq , Sadia Azam Khan , Mohammad Iqbal , Mohammad Tayyab Ahmad , Muhammad Umar (Journal of Rawalpindi Medical College, 2020)
Background: Psoriasis is a chronic inflammatory, immune mediated, provocative and challenging skin condition. It is a non-contagious but debilitating disease and a leading cause of socioeconomic burden on the health system. Objective: To evaluate the role of antioxidant levels, lipid peroxidation status and lipid profile in the etiology and degree of severity of psoriatic illness among psoriasis patients presenting in Dermatology department. Study Design: This study was carried out as a retrospective case control study. Place and duration of Study: It was carried out by the Department of Biochemistry, Basic Medical Sciences Institute (BMSI) in collaboration with Departmnt of Biochemistry, Khyber Medical College, Peshawar and Department of Skin and Venereal disease, Jinnah Post Graduate Medical Centre (JPMC) Karachi. Material and Methods: One hundred and twenty cases (n=130) of already diagnosed psoriasis patients were randommely and fifty healthy matched controls (n=50) of the same age and gender were included from the general population for comparison. Lipid profile including serum total cholesterol, TG, HDL-c and LDL-c levels were measured by enzyme colorimetric analysis on Micro Lab 300 (Merck & Germany). Antioxidant status SOD and lipid peroxidation status MDA were measured by ELISA technique. Statistical analysis was performed using SPSS software Version 16. In this analysis, a “p” value of less than 0.05 was considered to be significant. Results: The study showed significantly elevated levels of MDA, serum TG, total cholesterol and LDL-c levels in psoriatic patients in comparison with controls, whereas SOD levels and HDL-c levels were found to be significantly lower in psoriatic patients as compared to normal healthy matched controls. Conclusion: The findings of this study support the hypothesis that an imbalance in oxidant-antioxidant system may play a role in the etiology of psoriasis and the degree of severity of its presentation. The study also concluded that dyslipidemia was an observed risk factor for the development of cardiovascular diseases in psoriatic patients..